2020
DOI: 10.1101/2020.08.27.270967
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning Distance-Dependent Motif Interactions: An Explicitly Interpretable Neural Model of Genomic Events

Abstract: In most biological studies, prediction is used primarily to validate the model; the real quest is to understand the underlying phenomenon. Therefore, interpretable deep models for biological studies are required. Here, we propose HyperXPair (the Hyper-parameter eXplainable Motif Pair framework), a new architecture that learns biological motifs and their distance-dependent context through explicitly interpretable parameters that are immediately understood by a biologist. This makes HyperXPair more than a decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In line with this, RBPs have been shown by spaced k -mer counting approaches to often bind with multiple RBDs two separated cores with usually similar or identical motifs ( Dominguez et al , 2018 ; Jolma et al , 2020 ). Transcription factor motif discovery tools have been developed to learn co-occurrence of motif pairs in genomic sequences ( Toivonen et al , 2018 , 2020 ), and more recently, it was shown that distance dependent RNA motif pairs can be inferred from neural networks ( Koo et al , 2020 ; Quinn et al , 2020 ). However, transcription factor binding fundamentally differs from RBP binding as DNA can mediate cooperativity by propagating structural deformations induced by binding of proteins along the helix.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, RBPs have been shown by spaced k -mer counting approaches to often bind with multiple RBDs two separated cores with usually similar or identical motifs ( Dominguez et al , 2018 ; Jolma et al , 2020 ). Transcription factor motif discovery tools have been developed to learn co-occurrence of motif pairs in genomic sequences ( Toivonen et al , 2018 , 2020 ), and more recently, it was shown that distance dependent RNA motif pairs can be inferred from neural networks ( Koo et al , 2020 ; Quinn et al , 2020 ). However, transcription factor binding fundamentally differs from RBP binding as DNA can mediate cooperativity by propagating structural deformations induced by binding of proteins along the helix.…”
Section: Introductionmentioning
confidence: 99%
“…RBPs have further been shown by spaced k-mer counting approaches to often bind with multiple RNA-binding domains two separated cores with usually similar or identical motifs (6,13). A recent deep learning software is the only available one capable of learning distance dependent motif pairs (29).…”
Section: Introductionmentioning
confidence: 99%